Data from the PALS (Pregnancy and Lifestyle Study), a Community-Based Study of Lifestyle on Fertility and Reproductive Outcome. (10th November 2015) - Ford, Judith Helen
In order to assess the possible effects of lifestyle on fertility and pregnancy outcome, the PALS (Pregnancy and Lifestyle study) collected extensive data on a broad range of parameters termed 'lifestyle' from couples who were planning a natural (non-assisted) pregnancy in the coming months. There was no intervention. Participants were recruited over a six year period from 1988 to 1993 in response to extensive promotion in the local media. Male and female partners were interviewed independently and all interviews were conducted prospectively before the couple attempted to conceive. The result of each month of 'trying' was recorded and pregnancies were confirmed by urine tests and by ultrasound. The length of gestation of each pregnancy was recorded and pregnancies at term were classified with respect to weight. Multiple pregnancies and/or babies with congenital abnormalities have been excluded from the dataset. The data is stored as an xls file and each variable has a codename. For each of 582 couples there are 355 variables, the codes for which are described in a separate metadata file. The questionnaire based data includes information about households, occupation, chemical exposures at work and home, diet, smoking, alcohol use, hobbies, exercise and health. Recorded observations include monthly pregnancy tests and pregnancy outcomes.